Identifying mismatch repair‐deficient colon cancer: near‐perfect concordance between immunohistochemistry and microsatellite instability testing in a large, population‐based series. Issue 3 (11th October 2020) - Loughrey, Maurice B; McGrath, Jason; Coleman, Helen G; Bankhead, Peter; Maxwell, Perry; McGready, Claire; Bingham, Victoria; Humphries, Matthew P; Craig, Stephanie G; McQuaid, Stephen; Salto‐Tellez, Manuel; James, Jacqueline A
Abstract : Aims: Establishing the mismatch repair (MMR) status of colorectal cancers is important to enable the detection of underlying Lynch syndrome and inform prognosis and therapy. Current testing typically involves either polymerase chain reaction (PCR)‐based microsatellite instability (MSI) testing or MMR protein immunohistochemistry (IHC). The aim of this study was to compare these two approaches in a large, population‐based cohort of stage 2 and 3 colon cancer cases in Northern Ireland. Methods and results: The study used the Promega pentaplex assay to determine MSI status and a four‐antibody MMR IHC panel. IHC was applied to tumour tissue microarrays with triplicate tumour sampling, and assessed manually. Of 593 cases with available MSI and MMR IHC results, 136 (22.9%) were MSI‐high (MSI‐H) and 135 (22.8%) showed abnormal MMR IHC. Concordance was extremely high, with 97.1% of MSI‐H cases showing abnormal MMR IHC, and 97.8% of cases with abnormal IHC showing MSI‐H status. Under‐representation of tumour epithelial cells in samples from heavily inflamed tumours resulted in misclassification of several cases with abnormal MMR IHC as microsatellite‐stable. MMR IHC revealed rare cases with unusual patterns of MMR protein expression, unusual combinations of expression loss, or secondary clonal loss of expression, as further illustrated by repeat immunostaining on whole tissue sections. Conclusions: MSI PCR testing and MMR IHC can be considered to be equally proficient tests for establishing MMR/MSI status, when there is awareness of the potential pitfalls of either method. The choice of methodology may depend on available services and expertise.